FTAA and agriculture in the Andean community of nations. - OTERO, Manuel (1997)
Presents a brief summary of the evolution of the FTAA and the main negotiating positions. Reflects on the situation in which agriculture in the Andean region finds itself, and on the factors that could possibly help it compete in the new expanded market.